2009
DOI: 10.1111/j.1600-9657.2008.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated treatment to resolve a horizontal root fracture

Abstract: Root fractures are defined as those that involve cement, dentin and pulp, comprising from 0.5 to 7% of injuries in permanent dentition. Diagnosis is made through clinical and radiographic exams, the latter frequently being limited by the position of the fracture. Treatment varies according to the displacement and vitality of the fragments. The authors present a clinical case of recurrent trauma of tooth 21 causing a horizontal root fracture in the middle third. After several attempts at endodontic treatment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Clinical examination of root fractures should evaluate tooth color, sensitivity to percussion, mobility, and sensitivity to thermal stimulation (4). In our study, both cases showed slight mobility (grade 1), which can be explained by the cervical location of the fracture line, on at least one side of the root (7).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Clinical examination of root fractures should evaluate tooth color, sensitivity to percussion, mobility, and sensitivity to thermal stimulation (4). In our study, both cases showed slight mobility (grade 1), which can be explained by the cervical location of the fracture line, on at least one side of the root (7).…”
Section: Discussionmentioning
confidence: 58%
“…The upper central incisors are most often affected by horizontal root fractures (HRF), followed by the upper lateral incisors, as a result of trauma associated with accidents, sports injuries, or fights . Only 5% of root fractures occur in lower incisors . Diagnosis of HRF must be based on clinical findings, sensitivity tests, and radiographic examination.…”
mentioning
confidence: 99%
“…Reduction of the fragments and maintaining them in their original position allows the fracture to consolidate by formation of a callus that resembles dentin on the pulp side and that resembles dental cement on the periodontal ligament side. This healing, which is common in case of immature teeth and when the associated periodontal trauma is minimal, varies from 2-3 months in the best cases (1,13,14). The immobilisation splint is kept in place for 4-12 weeks if movement of the coronal segment persists upon removal of the restraint, and another immobilisation will have to occur for a longer period of time (5,11).…”
Section: Discussionmentioning
confidence: 99%
“…Root fractures are defined as fractures that involve dentin, cementum and the pulp, resulting in stretching or laceration of the pulp and/or periodontal ligament injury (rupture or compression) [4]. Root fractures are relatively rare trauma, comprising from 0.5% to 7.0% of injuries in permanent dentition [5]. Immature teeth with vital pulps rarely sustain horizontal root fractures [6].…”
Section: Introductionmentioning
confidence: 99%